Un nuevo reto a la Integralidad. - Bécquer Aguila, Jorge Luis; García Heredia, Gilda; Gispert Abreu, Estela de los Angeles (Revista Cubana de Estomatología, 2016)
One of the great achievements of the Cuban Stomatology in the last 30 years is the Oral Cancer Detection Program (PDCB), created in the decade of the eighties of the last century, thanks to the effort and dedication of a group of professionals led by Professor Julio César Santana Garay. This Program has reached greater coverage with the inclusion of the learning of its methodology in the study programs of the career, and with its implementation by the stomatologists in each of the health areas of the Cuban national territory. In our country, cancer is the first cause of death and of potential years of life lost; it is the cause that most lacerates the life expectancy at birth, and the first cause of mortality in the group of people over 60 years of age, so that every day increases the number of patients afflicted by this disease in the Cuban family. 1 Unfortunately, cancer of the head and neck is still an affectation that occurs in many people, and it is precisely the PDCB one of the tools that can help to change the adverse results that it can bring. Transmit information, clarify the aspects that may disturb patients and family members, work on community intervention projects that arrive in a simple and accessible way to local actors and decision-makers, making viable the management of some basic technical elements, for those who wish to work with Seriousness and rigor in this field may not be an easy or desirable task; but it constitutes a professional challenge for the basic health team of each community2 where complementary actions aimed at achieving the integrality of a task can be encouraged and facilitated, whose purpose is to achieve a reduction in the incidence of oral cancer. . Those who recognize the work of professionals who, like Dr. Santana, have begun and carry out the professional ethics and humanistic principles necessary to carry out this noble and worthy task, will not lose interest in the quality of life of patients diagnosed with the disease in any of their stages, as well as to watch over primary caregivers, their emotions or behaviors, their economy, physical symptoms, self-care, social life, relationship of couples, life project, physical appearance, rest and sleep. Cancer not only afflicts the patient who suffers it, but also considerably affects his family.3 The oncological patient with advanced cancer, like his family, goes through several stages of transformation in the confrontation of the disease. This interaction between the patient and his family is a complex relationship, in which the patient suffers the alterations of the family, and the family suffers from the patient.4 Health promotion, prevention tasks, active research, the creation of educational materials, the inclusion and prioritization of the topic in various family and social spaces, the identification of problems, the design of strategies, and their evaluation, can not be left in no one’s land or relapse on only one person.2 The feedback of the patient with oral cancer needs a revitalization that includes, in addition, to their primary caregivers, with the reception of the data regarding the behavior of the other oral diseases in those people, who by adverse special situations may have changed their styles of life. It is time to jump to an upper echelon, where true science reaches the population and is realized within it with real understanding and an extensive participation of experts and affections. It is time to propitiate that the dynamic overcomes the aesthetic, and that the totality implicitly involves the participation of all parties. It is important that the human does not forget the support, and the accompaniment, as it is also necessary that science does not neglect training or research.2 Being a reference in Latin America is a challenge for the Cuban Stomatology, and to face it we need to carry out more preventive actions, exchange opinions on the progress of the Program in our country, and undertake strategies in the search for greater effectiveness, monitor with zeal the ethics and professional performance, and assimilate experiences that make us orient a little more towards success in this task.